EAPH-09. POTENT CLINICAL AND RADIOLOGICAL RESPONSE TO LAROTRECTINIB IN FIRST CASE OF TRK FUSION HIGH GRADE GLIOMA. Issue 2 (22nd June 2018) - Ziegler, David; Tsoli, Maria; Tyrell, Vanessa; Cohn, Richard; Lau, Loretta; Cox, Michael; Cowley, Mark; Ekert, Paul; Marshall, Glenn; Haber, Michelle
Abstract: Genes encoding neurotrophin receptor kinases (TRK) have recently been implicated as an oncogenic driver in multiple tumor types including congenital fibrosarcoma, papillary thyroid cancer and adult glioblastoma. TRK fusions have been found in up to 40% of non-brainstem infant high grade gliomas (HGG), and play a critical role in tumorigenesis. Larotrectinib is the first and only selective pan-TRK inhibitor in clinical development. Larotrectinib is available as a liquid formulation and has been shown in a Phase 1 trial to be well tolerated in children, with high response rates in TRK fusion solid tumors. Here we report the first case of a pediatric HGG treated with larotrectinib. The patient was initially diagnosed at 5 months of age with a high-grade, right parietal tumor and treated in another institution as an ependymoma with intensive chemotherapy. Following a localized recurrence and resection at 2 years, the diagnosis of HGG was confirmed and treated with focal radiation therapy. By age 3, she developed further primary site tumor progression, and multiple metastatic subependymal nodules. Tumor profiling confirmed an ETV6-NTRK3 fusion. Compassionate access to larotrectinib treatment was provided, and led to rapid clinical improvement with gains in all developmental milestones over 4–6 weeks. After 2 cycles, MRI imaging confirmed near total resolution of primary and metastatic lesions. The patient continues on therapy and updated clinical and radiological results will be presented. This case represents a new paradigm for the treatment for pediatric patients with TRK fusion HGG. Enrolment to a global phase 2 trial is ongoing.